STANDARDIZATION OF ANTICONVULSANT POLYHERBAL FORMULATION BY PHARMACOGNOSTICAL, DNA FINGERPRINTING AND HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY COMBINED WITH CHEMOMETRICS - Janani, Hetal; Maji, Jayanta Kumar; Verma, Ashish (International Journal of Current Pharmaceutical Research, 2016)
Objective: The combination between the stem bark powder of Chirabilva and Veerataru is used ethno folklore for the management of anti-convulsion by tribal people. To standardise the evidently used polyherbal formulation in a systemic way for supporting the identity, quality, purity, safety and efficacy concern with modern technique. Methods: Microscopic anatomical examination and powder microscopy were performed fresh and dried plant materials respectively. The compound polyherbal formulation is processed by organoleptic characterization, macro-microscopic evaluation, physicochemical, phytochemical testing, DNA fingerprinting and high-performance thin-layer chromatography (HPTLC) profiling employing a standard methodology. Chromatographic fingerprinting after visualisation the data are exploited by multivariate chemometric technique. Results: Results of the experiment provided diagnostic characteristics to identify quality and purity and standardise the polyherbal formulation along with respective ingredients. The RAPD analysis of Dichrostachys cinerea and Holoptelea integrin folia showed some similar bands at the same base pair indicate the presence of genetical identity may take into consideration of the control the ingredients. HPTLC technique utilised to distinguish the ingredient and polyherbal formulation based on the presence or absence of certain target phytochemical (flavonoid, polyphenol, etc.) constituents, manifested as peaks or bands from the chemical fingerprint profiles. Visualized chromatographic profile of polyherbal formulation along with its constituents applying the multivariate chemometric technique is easily discriminated of respective retardation factor in principal component score space. Conclusion: The findings from this study will provide systemic evaluation for this anticonvulsant formulation and also serve as a master document to control the quality of polyherbal formulation. Keywords: Anticonvulsant, Chemometrics, DNA fingerprinting, HPTLC, Pharmacognosy